2011
DOI: 10.1007/s10936-011-9179-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Online Reading Paradigms: Eye Tracking, Moving-Window, and Maze

Abstract: This study compares four methodologies used to examine online sentence processing during reading. Specifically, self-paced, non-cumulative, moving-window reading (Just et al. in J Exp Psychol Gen 111:228-238, 1982), eye tracking (see e.g., Rayner in Q J Exp Psychol 62:1457-1506, 2009), and two versions of the maze task (Forster et al. in Behav Res Methods 41:163-171, 2009)--the lexicality maze and the grammaticality maze--were used to investigate the processing of sentences containing temporary structural ambi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
77
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 33 publications
14
77
0
2
Order By: Relevance
“…This means that the keypresses in the self-paced reading study lag behind eye fixations, whereas the reverse is less evident. Apparently, there is a stronger spillover effect in self-paced reading than in eye tracking, as is consistently found when comparing the two paradigms (e.g., Just, Carpenter, & Woolley, 1982;Witzel, Witzel, & Forster, 2012). In addition, the positive correlation between fixation durations at t and self-paced reading times at t + 1 could be due to parafoveal preview in the eye-tracking study.…”
Section: Reading Time Distributionssupporting
confidence: 58%
“…This means that the keypresses in the self-paced reading study lag behind eye fixations, whereas the reverse is less evident. Apparently, there is a stronger spillover effect in self-paced reading than in eye tracking, as is consistently found when comparing the two paradigms (e.g., Just, Carpenter, & Woolley, 1982;Witzel, Witzel, & Forster, 2012). In addition, the positive correlation between fixation durations at t and self-paced reading times at t + 1 could be due to parafoveal preview in the eye-tracking study.…”
Section: Reading Time Distributionssupporting
confidence: 58%
“…In fact, this version of the task could be accomplished on purely lexical grounds, without any reference to sentence structure or meaning. Despite this apparent difference, similar sentence processing effects have been revealed in both the G-maze and L-maze (see e.g., Forster et al, 2009;Witzel et al, 2012). Therefore, even though the different versions of this task might place different demands on the participants, they nevertheless seem to tap into comparable processing mechanisms.…”
Section: Methodsmentioning
confidence: 80%
“…In order to measure word-by-word reading times, a variant of self-paced reading was used: the maze task (Forster, 2010;Forster et al, 2009;Nicol, Forster, & Veres, 1997;Witzel, Witzel, & Forster, 2012). In this task, each sentence is presented as a sequence of choices between two alternatives, one of which is a possible continuation of the sentence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-script masked translation priming effects for non-cognates have been repeatedly shown for non-balanced sequential bilinguals, mainly occurring when primes belong to the native language and targets belong to the nonnative language (i.e., L1-to-L2 direction; see, among many others, Gollan, Forster, & Frost, 1997, for Hebrew-English combinations;Jiang, 1999, Jiang & Forster, 2001, and Witzel & Forster, 2012 (2010) for instance showed that balanced Basque-Spanish bilinguals permanently exposed to their two languages display significant and comparable masked translation priming effects in both language directions (see also Duñabeitia, Dimitropoulou, et al, 2010, for an EEG replication of these effects). The question under scrutiny in Experiment 2 is whether these masked translation priming effects in balanced simultaneous bilinguals (i.e., faster recognition of targets preceded by their translation equivalents in the other language as compared to unrelated primes) are modulated by the orthographic markedness of the briefly displayed masked words.…”
mentioning
confidence: 99%